A Journey of Local Wisdom - Yuliani, Naning; Fitriyah, Lilis; Laksmita, Shafira Angela Putri; Maulaya, Ahmad Husein (Proceedings of Annual Conference for Muslim Scholars, 2025)
Character education in children is crucial to develop from an early age by providing various stimulations and habituation patterns. This study aims to describe the implementation of local wisdom in meditation habits at RA Kasih Bunda Menganti Gresik as part of early childhood character education. The research method used is a qualitative case study approach with data collection through interviews, observation, and documentation. Data analysis uses time-series analysis, or data analysis based on the chronology of events over time. This study found that meditation activities were conducted every morning together with teachers sitting in a circle, holding hands, and closing their eyes, accompanied by the recitation of verses from the Quran. This activity had a significant impact on student behavior, clearly indicating that students were sufficiently prepared to participate in learning activities. In conclusion, this study contributes to the development of early childhood character education through meditation activities that can foster students' attitudes that are easily guided and independent in carrying out their activities in the classroom